Proteomic profiling identifies muscle-invasive bladder cancers with distinct biology and responses to platinum-based chemotherapy - A. Contreras-Sanz; G. L. Negri; M. J. Reike; H. Z. Oo; J. M. Scurll; S. E. Spencer; K. Nielsen; K. Ikeda; G. Wang; C. L. Jackson; S. Gupta; M. E. Roberts; et al. (Nature Communications)
Abstract Platinum-based neoadjuvant chemotherapy prior to radical cystectomy is the preferred treatment for muscle-invasive bladder cancer despite modest survival benefit and significant associated toxicities. Here, we profile the global proteome of muscle-invasive bladder cancers pre- and post-neoadjuvant chemotherapy treatment using archival formalin-fixed paraffin-embedded tissue. We identify four pre-neoadjuvant chemotherapy proteomic clusters with distinct biology and response to therapy and integrate these with transcriptomic subtypes and immunohistochemistry. We observe proteomic plasticity post-neoadjuvant chemotherapy that is associated with increased extracellular matrix and reduced keratinisation compared to pre-neoadjuvant chemotherapy. Post-neoadjuvant chemotherapy clusters appear to be differentially enriched for druggable proteins. For example, MTOR and PARP are over-expressed at the protein level in tumours identified as neuronal-like. In addition, we determine that high intra-tumoural proteome heterogeneity in pre-neoadjuvant chemotherapy tissue is associated with worse prognosis. Our work highlights aspects of muscle-invasive bladder cancer biology associated with clinical outcomes and suggests biomarkers and therapeutic targets based on proteomic clusters.